mtDNA mutations in human aging and longevity: Controversies and new perspectives opened by high-throughput technologies - Sevini, Federica; Giuliani, Cristina; Vianello, Dario; Giampieri, Enrico; Santoro, Aurelia; Biondi, Fiammetta; Garagnani, Paolo; Passarino, Giuseppe; Luiselli, Donata; Capri, Miriam; Franceschi, Claudio; Salvioli, Stefano (Experimental gerontology, 2014)
The last 30years of research greatly contributed to shed light on the role of mitochondrial DNA (mtDNA) variability in aging, although contrasting results have been reported, mainly due to bias regarding the population size and stratification, and to the use of analysis methods (haplogroup classification) that resulted to be not sufficiently adequate to grasp the complexity of the phenomenon. A 5-years European study (the GEHA EU project) collected and analyzed data on mtDNA variability on an unprecedented number of long-living subjects (enriched for longevity genes) and a comparable number of controls (matched for gender and ethnicity) in Europe. This very large study allowed a reappraisal of the role of both the inherited and the somatic mtDNA variability in aging, as an association with longevity emerged only when mtDNA variants in OXPHOS complexes co-occurred. Moreover, the availability of data from both nuclear and mitochondrial genomes on a large number of subjects paves the way for an evaluation at a very large scale of the epistatic interactions at a higher level of complexity. This scenario is expected to be even more clarified in the next future with the use of next generation sequencing (NGS) techniques, which are becoming applicable to evaluate mtDNA variability and, then, new mathematical/bioinformatic analysis methods are urgently needed. Recent advances of association studies on age-related diseases and mtDNA variability will also be discussed in this review, taking into account the bias hidden by population stratification. Finally, very recent findings in terms of mtDNA heteroplasmy (i.e. the coexistence of wild type and mutated copies of mtDNA) and aging as well as mitochondrial epigenetic mechanisms will also be discussed. •Aggregate effects of rare mtDNA mutations can be evaluated only on complete sequences.•Recurrent or sporadic mutations accumulated in OXPHOS genes may influence longevity.•NGS, large cohorts and matched controls are essential to spot association with phenotypes.•Big data analysis for mtDNA still lack adequate methods.